Magnetic Nanoparticles of Chitosan for Targeted Delivery System of Plasmids to the Lungs - Alvizo Báez, Cynthia Aracely; Luna Cruz, Itza Eloísa; Rodríguez Padilla, María Cristina; Alcocer González, Juan Manuel (2014)
One of the major problems of gene therapy is the efficient, specific, and targeted delivery as well as the safety of the materials used in such systems. The specific targeted delivery of genes to the lung offers the possibility to treat a variety of specific diseases. We developed chitosan nanoparticles with the plasmid pCEM-Luc, which contains a promoter activated by magnetic field. Nanoparticles of 200–250 nm obtained by ionic gelation with a 99% retention rate were transfected in B16F10 cells and in vivo in the lungs of Balb/c mice by intratracheal administration. We observed that an external magnetic field increased the expression of the luciferase reporter gene in B16F10 cells transfected with magnetic nanoparticles and inhomogenized lungs of mice which determined differences in levels of expression between different regions of the lungs (apical or distal and left or right). The highest levels of luciferase activity were observed in the apical left region. The magnetic nanoparticles prove an efficient delivery system to in vitro transfection of cells and lung tissue.